Answer:
b = -6
Step-by-step explanation:
Apply the exponent rule that
In this case, ![\frac{1}{y^{24}} = y^{-24}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7By%5E%7B24%7D%7D%20%20%3D%20y%5E%7B-24%7D)
Set that equal to
:
![(y^{b})^{4} = y^{-24}](https://tex.z-dn.net/?f=%28y%5E%7Bb%7D%29%5E%7B4%7D%20%3D%20y%5E%7B-24%7D)
Apply the exponent rule that
so now you get:
![y^{4b} = y^{-24}](https://tex.z-dn.net/?f=y%5E%7B4b%7D%20%3D%20y%5E%7B-24%7D)
Since the base is y for both sides of the equation, just set the exponents equal to each other and solve for b.
4b = -24
divide each side by 4 to get:
b = -6
Answer:
# AB is bisected by CD
# AE = 1/2 AB
# CE + EF = FD
Step-by-step explanation:
* Lets talk about the mid point
- The mid-point of a segment is divided the segment into two
equal parts
- The figure has line segment AB
- E is the mid-point of AB
∴ E divides the line segment AB into two equal parts
∴ AE = EB
∴ AE = 1/2 AB ⇒ (1)
- Any line passes through the point E will bisects the line segment AB
∴ AB is bisected by CD ⇒ (2)
∵ F is the mid-point of CD
∴ F divides the line segment CD into two equal parts
∴ CF = FD
∵ Point E lies on CF
∴ CE + EF = CF
∵ CF = FD
∴ CE + EF = FD ⇒ (3)
* There are three statements must be true (1) , (2) , (3)
# AB is bisected by CD
# AE = 1/2 AB
# CE + EF = FD
It’s BBBBBBBBBBBBBBBBBBBBBB
The value of x is 72
Each side increased by 20%
First simplify the square roots.
√25 is 5 and √16 is 4
so the equation is 3x5 + 4x4
15+16
31